“Men who love the oak trees”: services and care in the cork oak forests of Southern Andalusia - Javier Escalera-Reyes; Agustín Coca-Pérez (Ecology and Society)
Our article is aligned with the growing interest from the sustainability science in the need to broaden our view of the connections between humans and nature for better understanding them that helps to improve environmental governance systems. Our work aims to provide evidence that helps to overcome the dualistic and utilitarian prejudices that the ecosystem services framework presents on this issue, hindering its potential, both theoretically and practically. To this end, it is essential to incorporate the affective dimension that often permeates this relationship and turns it into care. Moreover, we do this in a social-ecological context such as that of the European Mediterranean, which is different from that of the non-western indigenous populations, of which we have examples that demonstrate the proactive role that people have played and continue to play in the construction and conservation of valuable ecosystems. We take as a case study the activities carried out by the people who work in the cork oak forests of southern Andalusia for their maintenance and for the extraction of cork. Drawing on the knowledge gained from a long period of mainly ethnographic re-search, we advocate incorporating the care practices, knowledge, and feelings that permeate the relationships that these workers have with the trees and the forest into the governance spaces of these landscapes as fundamental elements to achieve the sustainable management of cork oak forests. This is particularly relevant in a context marked by the decline in the socio-environmental conditions of these agroforestry social-ecological systems due to ageing of the trees and the diseases affecting them as a result of changes in use and management, aggravated by climate change.